Analysis of Joseph V. Mascelli's 5'C Cinematographic Technique On the movie All Quiet on the Wstren Front - Mu'minin, Ummul; Abidin, Kurniati; Wandi, Wandi (Palakka : Media and Islamic Communication, 2024)
This study discusses the analysis of Joseph V. Mascelli's 5'C cinematographic technique in the film All Quiet On the Westren Front. This study aims to find out how the application and nuances of the film All Quiet On the Westren Front are analyzed using Joseph v. Mascelli's theory of 5'C cinematographic techniques. The type of research used is qualitative descriptive which carries out an in-depth presentation of data by describing and summarizing the phenomenon that is the object of research with data that is how many words or pictures. This research uses a communication science approach and a qualitative approach. This study uses data collection techniques in the form of documentation that is analyzed using Joseph V. Mascelli's 5'C cinematography technique and qualitative data analysis techniques by Miles and Huberman. The results of the study show that in the film All Quiet On the Westren Front, Joseph V. Mascelli applies five elements of cinematography, including the camera angle is used to show the location so that it can describe the events that occur in the film, Contiunity to depict time and space with the use of Cutting in moving scenes can facilitate understanding the storyline in the film, Close up is used to show certain details and expressions can describe the emotions of the player and Composition on the placement of objects and elements in the film can direct the attention of the audience and produce interesting visuals.